PERIOD ESTIMATION OF TIME-LAPSE MICROGRAVITY MONITORING USING GAUSS THEOREM – CASE STUDY: KAMOJANG GEOTHERMAL FIELD - Lendriadi Agung; Mohammad Syamsu Rosid; Tofan Sastranegara; Haq, Fadhilaz Digdaya (GEOMATE Journal, 2023)
Maintaining the stability and continuity of steam production in the geothermal industry is a necessity. Mass changes in the reservoir due to geothermal production need to be monitored. Time-lapse microgravity measurement can be monitoring the effect of fluid extraction and injection process in geothermal wells. Inaccuracy of the gravity monitoring period can cause bias and inaccurate depictions of fluid dynamics and mass changes that occur in geothermal reservoirs. The aim of this study is to determine the appropriate period of time-lapse microgravity monitoring. Forward modeling from the Gauss theorem can be used to estimate the magnitude of the gravitational change anomaly in a certain period. With the current measurement capabilities, the estimation of the magnitude of the gravitational changes is when the value of the changes in gravity is greater than 25 µGal between two monitoring measurement periods. In the Kamojang geothermal field, it was found that the optimal gravity monitoring period is conducted every 11-13 months to optimally describe changes in mass and fluid dynamic reservoir.